Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Roti Mr Bread Di Indomaret Timbul Cabang Parung - Nur Ropandi; Arif Siaha Widodo (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine how much influence price and product quality have on purchasing decisions for Mr. Bread at Indomaret Timbul Parung Branch. This study uses a quantitative approach with a research sample of 94 respondents and Probability Sampling sampling technique, as well as data collection techniques through distributing questionnaires. The data analysis method used is data instrument test, classical assumption test, simple and multiple linear regression tests, correlation coefficient and determination, and hypothesis testing. The results showed that, Price (X1) had an effect on Purchasing Decisions by 49% while the remaining 51% was influenced by other factors, Product Quality (X2) had an effect on Purchasing Decisions by 49.6% while the remaining 50.4% was influenced by other factors, Price (X1) and Product Quality (X2) had a significant effect on Purchasing Decisions (Y) with the regression equation Y = 12.368 + 0.225 X1 + 0.554 X2